Cervical-Vaginal Microbiome and Associated Cytokine Profiles in a Prospective Study of HPV 16 Acquisition, Persistence, and Clearance - Moscicki, Anna-Barbara; Shi, Baochen; Huang, Hazel; Barnard, Emma; Li, Huiying (Frontiers in Cellular and Infection Microbiology, 2020)
Cervical infections with human papillomavirus (HPV) are largely benign with most being transient whereas persisting infections are key to the development of cervical cancers. Similar to other mucosal sites, it is expected that the local microbiome plays a significant role in shaping the immune response responsible for HPV clearance. Using cervical wash repository samples from a prospective study of HPV in women, this study investigates the microbiome and its associated inflammatory milieu during HPV 16 pre-acquisition, persistence and clearance states. For comparison, samples from women with no history of HPV ever during the study period were selected. We showed that 9 of 13 inflammatory cytokines were found to be significantly increased in the immediate post-clearance visit compared to the pre-acquisition or infection visits. Gardnerella vaginalis was associated with higher levels of inflammatory cytokines. Women with no history of HPV infection had similar cytokine profiles as those with HPV 16 post-clearance. This in vivo study documented an immune response shortly after HPV 16 clearance. G. vaginalis appeared to be involved in shaping this immune response. The appearance of G. vaginalis may have resulted from a shift from anti-microbial to anti-viral immune response with loss of bacterial control. The similar high levels of cytokines seen in women with no history of HPV suggest that a certain level of inflammatory surveillance is required to maintain an HPV negative state. This data may inform therapies such as probiotics or pro-inflammatory agents for treatment of persistent HPV.